Saami and Berbers – an unexpected mitochondrial DNA link - ACHILLI, ALESSANDRO; RENGO, CHIARA; BATTAGLIA, VINCENZA; PALA, MARIA; OLIVIERI, ANNA; FORNARINO, SIMONA; BENERECETTI, AUGUSTA SILVANA; SEMINO, ORNELLA; TORRONI, ANTONIO; MAGRI C; SCOZZARI R; BABUDRI N; et al. (The American Journal of Human Genetics, 2005)
The sequencing of entire human mitochondrial DNAs belonging to haplogroup U reveals that this clade arose shortly after the "out of Africa" exit and rapidly radiated into numerous regionally distinct subclades. Intriguingly, the Saami of Scandinavia and the Berbers of North Africa were found to share an extremely young branch, aged merely approximately 9,000 years. This unexpected finding not only confirms that the Franco-Cantabrian refuge area of southwestern Europe was the source of late-glacial expansions of hunter-gatherers that repopulated northern Europe after the Last Glacial Maximum but also reveals a direct maternal link between those European hunter-gatherer populations and the Berbers.